2021
DOI: 10.1371/journal.pone.0255243
|View full text |Cite
|
Sign up to set email alerts
|

Perception of breast cancer risk factors: Dysregulation of TGF-β/miRNA axis in Pakistani females

Abstract: Breast cancer poses a serious health risk for women throughout the world. Among the Asian population, Pakistani women have the highest risk of developing breast cancer. One out of nine women is diagnosed with breast cancer in Pakistan. The etiology and the risk factor leading to breast cancer are largely unknown. In the current study the risk factors that are most pertinent to the Pakistani population, the etiology, molecular mechanisms of tumor progression, and therapeutic targets of breast cancer are studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…Null parity increases the risk of breast cancer, 14 however, in this study 94.4% of patients were parous. Similarly, a study conducted by Ahmed F et al 15 in Pakistan reported 93% breast cancer patients as parous. About 84% patients were breastfeeding their children, contrary to earlier report that breastfeeding for one year reduces breast cancer by 4.3%.…”
Section: Discussionmentioning
confidence: 78%
“…Pre-menopausal and menopausal patients found in this study were 50.8% and 49.2% respectively. Similarly, Ahmed F et al 15 reported 54.74% cancer in pre-menopausal patients. Patients with a family history of breast cancer were found to have high risk of breast cancer (OR: 4.3186 [1.7336 to 10.7581] p value =0.0017).…”
Section: Discussionmentioning
confidence: 81%
“…A study was conducted to predict the correlation of miRNAs with the grade and stage of cancers in population of Pakistan. Effect of miRNA on TGF-beta pathway was studied via TargetScanHuman and correlation was depicted through Mindjet Manager 22 .…”
Section: Mirnasmentioning
confidence: 99%